2011
DOI: 10.1136/vr.d4636
|View full text |Cite
|
Sign up to set email alerts
|

Review of bacterial and fungal culture and sensitivity results from reptilian samples submitted to a UK laboratory

Abstract: Reptiles are increasingly kept as pets in the UK and the majority of animals presented for veterinary attention have conditions with a bacterial basis, either as a primary infection or secondary to husbandry deficiencies. Culture and sensitivity tests can provide useful information for selecting treatment protocols, but the lack of published data reviewing the normal reptilian microflora means interpretation of results is subjective. This study publishes the results of culture and sensitivity results from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
1
22
0
5
Order By: Relevance
“…Normal conjunctival flora has been described in chelonians such as turtles and tortoises . Previous studies in sea turtles have reported conjunctival bacterial flora in sick animals .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal conjunctival flora has been described in chelonians such as turtles and tortoises . Previous studies in sea turtles have reported conjunctival bacterial flora in sick animals .…”
Section: Discussionmentioning
confidence: 99%
“…The contact of some species of reptiles with humans motivated studies on the microbiota that these animals harbor and their antibiotic resistance . The indiscriminate use of antimicrobials and its inappropriate discard in the aquatic environment, as well as natural resistance may increase the occurrence of multiresistant bacteria, which have been reported in birds, reptiles, and mammals from aquatic environments …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic mycotic diseases such as histoplasmosis, coccidioidomycosis, and cryptococcosis are rarely seen in reptiles (55). Fungal diseases may be promoted by immune-compromising conditions, such as husbandry deficiencies or inappropriate temperatures, humidity, or enclosure hygiene (60,61). Furthermore, reptiles are becoming more popular as companion animals and are therefore presented more frequently to veterinary care (62).…”
Section: Reptilesmentioning
confidence: 99%
“…Destas, uma (7,14%) foi classificada como baciliforme aeróbio uma (7,14%) Neste contexto, o simples reconhecimento das bactérias que ocupam estes ambientes, na necessidade de instalação de tratamento frente a ocorrência de processos infecciosos torna-se de pouca valia, principalmente em relação a escolha de antimicrobianos para a solução destes casos, pois sabidamente, muitas bactérias podem ser sensíveis a alguns desses fármacos, porém, segundo Charrual et al (2012), algumas cepas ou espécies de bactérias podem não ser afetadas, ou simplesmente demostrarem resistência aos mesmos através de vários mecanismos primários, que podem atuar de forma individual ou múltipla. Desta forma, a realização de experimentos envolvendo testes de perfil de susceptibilidade provem melhores resultados e informações importantes em relação à escolha dos antimicrobianos, devendo ser realizados antes do início de qualquer tratamento (BASSETTI; VERDADE, 2014), sendo de grande relevância clínica (CUSHING et al, 2011).…”
Section: Resultsunclassified